Plastoelastic Analysis Of Bearing Capacity For Soil Anchor - Hui Yongning (Deep Foundations Institute, 1991)
This paper presents a simulating test of constitutive relation of soil anchor in laboratory and puts forward a new plastoelastic mechanical model, on which a new calculating formula of elastic and plastic limit bearing capacity for soil anchor is suggested and two engineering projects verify that this method is adaptable.